Evaluation of Patients with Macrocytosis - Elkıran, Tamer; Aygen, Bilge (Fırat University, 2001)
Macrocytosis is a common laboratuary finding with the increase of mean cell volume of the red blood cells. Although the normal range varies slightly from one laboratory to another, mean cell volume values exceeding 100 femtolitres generally shows the presence of macrocytosis. Macrocytic anemia is due to different causes and the most frequent causes are megaloblastic anemia and alcoholism. Macrocytic anemia split into two groups as megaloblastic and nonmegaloblastic anemia. Neutrophil hypersegmentation and macroovalocytosis on the blood film are the most sensitive and specific for megaloblastic anemia. The red cells are usually round rather than oval and the neutrophil hypersegmentation are not showed in the nonmegaloblastic anemia.

Makrositoz, ortalama eritrosit hacmindeki artış olup sık görülen bir laboratuar bulgusudur. Laboratuarlar arasında farklılıklar olmasına rağmen 100 femtolitrenin üzerindeki ortalama eritrosit hacmi, makrositoz olarak değerlendirilir. Makrositozun en fazla nedeni olarak megaloblastik anemiler ve alkolizm sorumlu tutulmuştur. Makrositik anemiler, megaloblastik ve megaloblastik olmayan anemi olarak iki gruba ayrılır. Periferik yaymada nötrofil hipersegmentasyonu ve makroovalositoz megaloblastik aneminin en spesifik ve sensitif bulgularındadır. Megaloblastik olmayan olgularda eritrositler ovalden ziyade yuvarlaktır ve nötrofil hipersegmentasyonu görülmez.
MAKROSİTOZLU OLGULARIN DEĞERLENDİRİLMESİ